Ultimum Remedium dalam Bidang Lingkungan Hidup - Lidya Suryani Widayati (Fakultas Hukum Universitas Islam Indonesia, 2015)
The law enforcement in environmental field can be done both through administrative/civil law and criminal law. In recent developments, the law enforcement in environmental field tends to shift towards premium remedium. This research aims at analyzing principle feasibility of ultimum remedium in the environmental field through normative law research or literary law research by applying juridicial approach. This research concludes that criminal law enforcement in environmental field case by still referring to the principle of ultimum remedium is no longer worth to be held as the environmental cases lead to some harmful impacts on the nature and people’s life.